Assessing Business Sustainability Level: The Case of BIOMASS Company - Berro, Zahraa (Technium Social Sciences Journal, 2021)
In light of the acceleration towards adopting the principles of sustainability as a result of climate change and the importance of preserving the environment, a group of companies emerged that tried to exploit these conditions in a bad way, which prompted them to colorize their business under the pretext of showing themselves as a sustainable company. For this reason, this study sought to evaluate one of the most prominent companies in Lebanon called “BIOMASS” which is concerned with organic products, using the typology of Dyllick & Muff that categorized the business into three levels of sustainability. The study adopted the qualitative approach in order to frame the extraction of information from the company, in addition to some desk research. In the conclusion of the research, it was found that the company bears the characteristics of sustainability in a right and striking manner.